Pendulum Experiments Using A Smartphone-Based Phyphox: An Application of Basic Physics Experiment Course During Covid-19 - Jesi - Pebralia (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2021)
During the lockdown period and PSBB of Covid-19, all student activities in classroom were eliminated, both activities in the form of theoretical lectures in class and practicum in the laboratory. All learning and teaching activities are carried out online using the Learning Management System (LMS) which is applied to each school and college. Practical activities carried out online and remotely require educators to find the right method so that learning objectives can be achieved as well as conventional learning. The purpose of this study is to provide an overview of one form of basic physics practicum that can be used in remote learning, especially during the Covid-19 pandemic. The topic chosen was pendulum motion using a smartphone based on the Phyphox application. The results obtained show the suitability of data graphs generated from practicum using smartphones and theoretical calculations with an R square value of 0.998. So that smartphones can be used as a tool for basic physics practicum in remote learning. Keyword: covid-19, Phyphox, remote learning, pendulum, physics experiment